Aboveground biomass, productivity and carbon sequestration in Rhizophora stylosa mangrove forest of Southeast Sulawesi, Indonesia - Kangkuso Analuddin; Kadidae La Ode; Muhammad Yasir Haya La Ode; Septiana Andi; Sahidin Idin; Syahrir La; Saban Rahim; Abdul Fajar La Ode; Nadaoka Kazuo (Society for Indonesian Biodiversity, 2020)
Abstract. Analuddin K, Kadidae LO, Haya LOMY, Septiana A, Sahidin I, Syahrir L, Rahim S, Fajar LOA, Nadaoka K. 2020. Aboveground biomass, productivity and carbon sequestration in Rhizophora stylosa mangrove forest of Southeast Sulawesi, Indonesia. Biodiversitas 21: 1316-1325. This study was aimed at analyzing the trends of aboveground biomass (AGB), productivity and carbon sequestration of Rhizophora stylosa Griff. forest in Rawa Aopa Watumohai National Park (RAWNP), Southeast Sulawesi, Indonesia. The DBH was the best predictor for partial and whole AGB of R. stylosa trees. The mean AGB was 562.76 ton ha-1. The yearly biomass increment of living trees, biomass increment of whole stands, standing dead biomass, and litterfall in R. stylosa forest were estimated as 52.87, 50.09, 2.78 and 12.00 ton ha-1, respectively, while its net primary production was about 64.88 ton ha-1 yr-1 indicating higher mangrove productivity. The total carbon stock in R. stylosa forest was 264.50 ton ha-1, while the annual net carbon budget, carbon gain and carbon input in R. stylosa forest was 23.54, 24.85 and 5.64 ton ha-1. However, the total CO2 stored in R. stylosa forest was 969.83 ton ha-1, while the annual of net CO2 uptake, CO2 gained and CO2 input was 86.33, 91.12 and 20.86 ton ha-1. The higher carbon sequestration and CO2 uptake in R. stylosa forest indicate its significant role in the global carbon accumulation and reducing atmospheric CO2.